TANTANGAN PENDIDIKAN ISLAM DI ERA GLOBALISASI - Fadliana, Nyayu Afriyani Nur; Harto, Kasinyo; Amilda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the challenges of Islamic Education in the era of globalization. Facing the challenges of modernity, Islamic education must take strategic steps by first building an integrative scientific paradigm as an answer to the dichotomy of science. The research method used is qualitative with a literature approach or library research. Data collection techniques are a way to understand and study the terrorists from various literary sources related to the literature that has been carried out in the literature. . The results of the study show that there are three main challenges currently faced by Islamic education, namely the advancement of science and technology, democratization, and moral decadence. In essence, Islamic educational institutions must reform their curriculum in order to prepare superior human resources and have competitiveness in the face of global competition.